Recent Progress of 2D Nanomaterials for Application on Microwave Absorption: A Comprehensive Study - Kallumottakkal, Muhammed; Hussein, Mousa I.; Iqbal, Muhammad Z. (Frontiers in Materials, 2021)
Rapid advancements and wide spread of microwave- and RF-communication systems over the years, have led to an abundant increase in electromagnetic energy radiation in our living environment. Such increase in microwave sources is due to the development and advancement in communication techniques (mobile phones, laptops, antennas for aeronautics or automobile) and electronic warfare in the military field (radar, Satellite). Recently research efforts are focused on finding solutions to guarantee protection from electromagnetic (EM) radiations. The EM absorbing materials are used to overcome these issues to ensure public protection as well as safe military operations. Various types of EM absorbing materials comprising of composite materials have been progressively developed and researched. This kind of materials is developed by impeding absorbing charges (magnetic or dielectric) into a host matrix material. Recently, carbon allotropes such as graphene, MXenes, carbon nanotubes (CNTs) and carbon fiber have attracted increasing attention owing to their EMI shielding characteristics and lightweight. This work presents a comprehensive study on the recent research progress on the application of nanomaterials for electromagnetic shielding and absorption. The review will cover microwave absorption mechanism and absorption performance using graphene, MXenes, carbon nanotubes (CNTs), carbides, and ferromagnetic metals. Overall, the review will present a timely update on the research progress of microwave absorption performance of various nanomaterials.